Penerapan Strategi Pemasaran dan Kualitas Pelayanan Delivery terhadap Minat Purchase Decision Konsumen UMKM Kerajinan Tangan Toko Serba: - Eva Latifatul Haziza; Ida Bagus Nyoman Udayana (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to find out how the marketing strategy is applied by the MSME Convenience Store, and how the quality of the delivery service for handicrafts at the MSME Convenience Store and how consumer purchasing decisions are made at the MSME handicraft at the Giwangan Convenience Store. This research is a quantitative study using survey methods until the population in the study is the consumer of Handicrafts in a department store. Collecting data using a questionnaire method that has been tested for validity and reliability. The data that has been collected is then tested for data, model testing and hypothesis testing. SPSS is used for data analysis and for taking a sample of 50 people so that the validity and reliability can be tested. Based on the results of the analysis and discussion, the authors conclude that marketing strategy and service quality together have a positive and significant effect on consumer purchasing decisions at the Yogyakarta Giwangan Handicraft Shop. The keywords: Marketing strategy, Service Quality on delivery, and Purchase Decision.